The role of real-time ultrasound in the assessment and management of preterm labour - Castle, Bruce M (Department of Obstetrics and Gynaecology, 2017)
In this thesis the use of real-time ultrasound in the assessment and management of preterm labour has been studied, with particular reference to the observation of fetal breathing movements, gross fetal body movements and the state of the uterine cervix. In addition, a longitudinal analysis of the trends in preterm labour in the John Radcliffe Hospital in Oxford between 1973 and 1981 has been performed. Finally, an attempt has been made to clarify the relationship between prostaglandin E2 and fetal breathing movements. The analysis of the trends in preterm labour in Oxford has shown that the incidence of preterm delivery remains unaltered. Of these patients, however, those eligible for tocolytic therapy (unexplained spontaneous preterm labour) form a small proportion. The incidence of extreme prematurity in this group is very low and the neonatal outcome is good. The presence or absence of Fetal Breathing Movements (FBM) by defined criteria is shown to be a highly sensitive index of whether the preterm labour is going to progress to delivery or not in singleton pregnancies with intact membranes. Its significance is lost when the membranes are ruptured and in multiple pregnancies. In pregnancies complicated by antepartum haemorrhage the presence or absence of Fetal Breathing Movements does not predict further haemorrhage leading to delivery. Fetal Breathing Movement status on admission bears no relationship to neonatal outcome and gives no indication of the presence of intrauterine infection. Silent chorioamnionitis has been highlighted as an important cause of "unexplained" preterm labour. Gross Fetal Body Movements (FM) are shown to give no early indication of impending preterm delivery. Evidence is presented to suggest that significant diminution in Fetal Movements is related to poor neonatal outcome. Ultrasonic measurement of the uterine cervix has been found to be technically feasible but of no benefit in the diagnosis of ongoing preterm labour. The relationship between prostaglandin E2 (PGE2) and the cessation of fetal breathing movement has been approached by elucidating the maternal absorption of PGE2 from a vaginal pessary. This then enabled me to sample fetal blood at the time of maximal maternal concentrations (the time we expect the fetal concentration to be greatest). This was performed by fetoscopy and demonstrated that a significant rise in fetal bicycleprostaglandin-E-metabolite (bicyclo-PGEM) occurs following maternal vaginal administration of PGE2. Using this information FBM has been assessed two and a half hours following the vaginal administration of PGE2. Although inconclusive, no reduction in FBM was demonstrated. as the bicyclo-PGE metabolite is used to assess PGE levels, this evidence decreases the probability that PGE mediates the reduction in FBM with the onset of labour.